An enumerative procedure for identifying maximal covers - Muñoz, S. (2003)
In this paper we present an enumerative procedure for identifying all maximal covers from the set of covers implied by a 0-1 knapsack constraint. The inequalities induced by these maximal covers are not dominated by the inequality induced by any other cover implied by the knapsack constraint. Thus, their identification can help to tighten 0-1 models. On the other hand, we present an improvement on a procedure taken from the literature for identifying certain maximal covers. Some comparative computational experiments where both procedures have been applied to randomly generated knapsack constraints are also reported.